Enhancement Mechanism of the Difference of Hydrophobicity between Anode and Cathode Active Materials from Spent Lithium-Ion Battery Using Plasma Modification - Dong, Lisha; Tong, Zheng; Wang, Xuexia; Bu, Xiangning (American Chemical Society, 2024)
In the context of resource utilization of spent lithium-ion batteries (LIBs), low-temperature plasma modification has the advantages of high efficiency and nonpollution over traditional recycling pathways. In this work, the technique of degrading the binder in electrode materials with low-temperature plasma is proposed to solve issues of poor direct flotation performance of anode and cathode materials and a low recovery rate. First, the analysis of contact angle measurement is carried out; second, the effect of low-temperature plasma on the difference of hydrophobicity of anode and cathode materials is verified by the results of particle-bubble adhesion, the recovery, and kinetics of single mineral flotation tests; finally, the mechanism of low-temperature plasma surface modification of exfoliated electrode materials is further characterized by X-ray diffraction, scanning electron microscope, and energy-dispersive X-ray spectroscopy, Fourier transform infrared, and X-ray photoelectron spectroscopy. Results show that low-temperature plasma oxidizes and degrades the binder through high-energy particles with the generated strong oxidizing active substances (•OH, •O, O3, etc.), making the original surface of anode and cathode materials exposed, which in turn increases the difference of hydrophobicity between the two and improves the flotation separation performance.